Iatrogenic vs. Spontaneous Preterm Birth: A Retrospective Study of Neonatal Outcome Among Very Preterm Infants - Chen, Xi; Zhang, Xiaoli; Li, Wenhua; Li, Wendong; Wang, Yong; Zhang, Shan; Zhu, Changlian (Frontiers in Neurology, 2021)
Objective: Preterm birth is a leading contributor to childhood morbidity and mortality, and the incidence tends to increase and is higher in developing countries. The aim of this study was to analyze the potential impact of preterm birth in different etiology groups on neonatal complications and outcomes and to gain insight into preventive strategies. Methods: We performed a retrospective cohort study of preterm infants less than 32 weeks' gestation in the Third Affiliated Hospital of Zhengzhou University from 2014 to 2019. Preterm births were categorized as spontaneous or iatrogenic, and these groups were compared for maternal and neonatal characteristics, neonatal complications, and outcomes. All infants surviving at discharge were followed up at 12 months of corrected age to compare the neurodevelopmental outcomes. Results: A total of 1,415 mothers and 1,689 neonates were included, and the preterm population consisted of 1,038 spontaneous preterm infants and 651 iatrogenic preterm infants. There was a significant difference in the incidence of small for gestational age between the two groups. Infants born following spontaneous labor presented with a higher risk of intraventricular hemorrhage, whereas iatrogenic preterm birth was associated with higher risk of necrotizing enterocolitis and coagulopathy and higher risk of pathoglycemia. There was no difference in mortality between the two groups. Follow-up data were available for 1,114 infants, and no differences in neurologic outcomes were observed between the two preterm birth subtypes. Conclusions: Preterm births with different etiologies were associated with some neonatal complications, but not with neurodevelopmental outcomes at 12 months of corrected age.